Innovation in Teams: The Role of Psychological Capital and Team Learning - Dimas, Isabel Cristina Dórdio (2022)
The main purpose of the present research was to analyze the relationship between team psychological capital and innovation, considering team learning as a mediating variable. A field survey was carried out, which included 124 work teams belonging to organizations from different sectors of activity. Hypotheses were tested through PROCESS. Results supported a direct positive relationship between team psychological capital and team innovation and an indirect influence of team psychological capital on team innovation, through team learning. The findings of this study highlight the role of team learning as an intervening process between team psychological capital and team innovation. Accordingly, managers should seek to develop team psychological capital and learning behaviors among their teams to promote innovation.